2019
DOI: 10.1038/s41419-019-1856-y
|View full text |Cite|
|
Sign up to set email alerts
|

SOCS5 inhibition induces autophagy to impair metastasis in hepatocellular carcinoma cells via the PI3K/Akt/mTOR pathway

Abstract: SOCS5 is a member of the suppressor of cytokine signaling (SOCS) protein family with important yet incompletely understood biological functions in cancer. In hepatocellular carcinoma (HCC), controversial tumor-promoting and tumor-suppressive roles of SOCS5 have been reported. Our study aims to unravel novel functions of SOCS5 in HCC, especially that affecting metastasis. We examined the expression levels of SOCS5 in HCC using publicly available datasets, and in our patient cohort, using quantitative real-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
83
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(92 citation statements)
references
References 25 publications
6
83
0
Order By: Relevance
“…Autophagy is also called programed cell death type II, which is different from the apoptotic type I death pathway (Choi et al, 2013). It is a highly conserved catabolic process that maintains cellular homeostasis by targeting damaged proteins or organelles to lysosomal compartments for degradation (Zhang et al, 2019). Autophagy has potential roles in radioresistance of cancer cells such as colorectal cancer, breast cancer, glioma, and pancreatic cancer (Yao et al, 2003;Chaachouay et al, 2011Chaachouay et al, , 2015Wang et al, 2013;Koukourakis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Autophagy is also called programed cell death type II, which is different from the apoptotic type I death pathway (Choi et al, 2013). It is a highly conserved catabolic process that maintains cellular homeostasis by targeting damaged proteins or organelles to lysosomal compartments for degradation (Zhang et al, 2019). Autophagy has potential roles in radioresistance of cancer cells such as colorectal cancer, breast cancer, glioma, and pancreatic cancer (Yao et al, 2003;Chaachouay et al, 2011Chaachouay et al, , 2015Wang et al, 2013;Koukourakis et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These ndings indicate that autophagy plays an essential role in the process of Aurora-B affecting the ability of motility and invasive in OS cells. Autophagy is reported to inhibit cell migration by accelerating the degradation of MMP family proteins (26,27), therefore, we sought to determine the MMP2 protein levels in Aurora-Bknockdown OS cells with or without CQ treatment. Results showed that the suppression of MMP2 expression due to Aurora-B knockdown could be restored by CQ treatment (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The self-protection mechanism of autophagy occurs in unfavorable environment, which is closely related to the occurrence and development of tumor [8]. For instance, autophagy can affect the progression of HCC by regulating the expression of other factors or signaling pathways, such as RAC1, NF-κB, and PI3K pathways [9][10][11]. However, the specific molecular mechanism between HCC and autophagy remains unclear.…”
Section: Introductionmentioning
confidence: 99%